Penerapan Metode Importance Performance Analysis (IPA) Dalam Mengukur Tingkat Kepuasan Masyarakat Terhadap Kinerja Pelayanan Di Kantor Camat Kecamatan Lebong Tengah - Wika Apriza; Ila Yati Beti; Desi Mahdalena (Jurnal Media Infotama, 2025)
Measuring the level of community satisfaction at the Central Lebong Sub-District Head Office still uses a complaint box, where people can write suggestions on a piece of paper and then enter the suggestion through the box provided with two options, namely satisfied and dissatisfied. This is certainly less effective and takes a long time in measuring the level of community satisfaction due to the absence of a definite indicator in assessing satisfaction with service performance at the Central Lebong District Head Office. The application of the Importance Performance Analysis (IPA) method in measuring the level of community satisfaction with service performance at the Central Lebong Sub-District Head Office can assist administrators in managing data on the assessment of community satisfaction with service performance at the Central Lebong Sub-District Head Office, can provide information on the level of community satisfaction with service performance at the Central Lebong Sub-District Head Office, and can facilitate the community, especially those in the Central Lebong Sub-District area, in providing an assessment of satisfaction with service performance at the Central Lebong Sub-District Head Office. The application of the Importance Performance Analysis (IPA) method in measuring the level of community satisfaction with service performance at the Central Lebong Sub-District Head Office was built web-based using the PHP programming language and MySQL database which can be accessed via the url link https://surveikecamatanlebongtengah.online/. Based on the tests that have been carried out, it is found that this application is very helpful in managing and evaluating data on community satisfaction assessment of services at the Sub-District Head Office of Central Lebong District so that the level of community satisfaction is known and this application can be used as a forum for the community in providing community satisfaction assessment of services at the Sub-District Head Office of Central Lebong District.